350. Measurement of secondary X-rays for radiation protection applications in a diagnostic department. (December 2018) - Ostinelli, A.; Duchini, M.; Cacciatori, M.; Frigerio, M.; Vassena, A.; Molinari, P.
Abstract : Purpose: In the X-ray interaction with matter, the absorbed dose is a kV function. While the multimeters for the primary beam provide a dose response independent from the voltage (±5%), the ion chambers used for the secondary radiation do not meet this requirement. An evaluation of the possibility to measure scatter fields with the R100 external detector of the RTI PIRANHA multimeter was carried out, by comparing its measurements with the ones provided by other survey meters. Methods: Scattered fields measurements were performed on a GMM-OPERA X-ray unit and a 30 × 30 × 15cm 3 plexiglas phantom was used to simulate the patient. The R100 data were compared to those measured by the ATOMTEX AT-1123 plastic scintillator and the PTW STEP OD-01 and Ludlum-9DP ionization chambers. Furthermore, an ORTEC NaI(Tl) detector was used to measure the scattered radiation spectra (Fig. 1) as a function of the voltage (40–125 kV). The ACCREDIA calibration factors were applied to the ionization chambers readings and specific conversion factors were used to convert R100 kerma in H*(10). The secondary radiation as a function of voltage (50–110 kV), phantom distance (50–150 cm) and field size (10 × 10-34 × 34cm 2 ) was characterized. Results: As expected, the ATOMTEX and Ludlum readings were strongly affected by saturation effects. The STEP data were slightly lower compared to the R100 ones, but both were repeatable and linear (see Fig. 2) and allowed to completely describe the scatter field for various exposure conditions. For the tube potential range of interest the spectrum mean energy varied from 24 to 60 keV. Conclusions: The data analysis showed that the H*(10) differences observed with the various instruments could result in not negligible errors. The comparison with the STEP results suggested that the R100 external probe of the RTI PIRANHA multimeter, already in use for quality control tests, can be use to measure secondary radiations in radiology.